The Design of Religious Value-Based Teaching Materials in Increasing Students’ Learning Achievement Elementary School - Sari, Yunita; Yustiana, Sari; Fironika, Rida; Ulia, Nuhyal; Iasha, Vina; Setiawan, Bramianto (Jurnal Basicedu, 2022)
This study aimed to develop a product of picture story teaching materials containing religious values. The aim is to determine the validity and practicality. The existing problems are the lack of available learning resources in schools, teaching materials in schools are not fully available, student achievement is still low. This study uses the ADDIE development model, the stages are Analysis, Design, Development, Implementation, and Evaluation. the results of the validation of 3 validators obtained an average result of 0.875 with the category "High validation". (2) The practicality of picture story teaching materials containing religious values obtained an average percentage of 95.5% in the "very feasible" category from the teacher's response and student responses obtained a percentage of 93.3% with the "very feasible" category. Based on these results, illustrated story teaching materials containing religious values can be said to be valid and practical to improve the learning achievement of 1st-grade elementary school students.